2021
DOI: 10.1108/jcm-10-2019-3460
|View full text |Cite
|
Sign up to set email alerts
|

Developing brand advocacy through brand activities on Facebook

Abstract: Purpose This paper aims to investigate how brands’ social media activities (credible content delivery, co-creation and responsiveness) impact brand advocacy. The paper also examines the influence of brand advocacy on purchase intentions of brand advocates and the moderating effect of the amount of time spent on Facebook on the relationship between brand advocacy and purchase intentions. Finally, the moderating effect of brand type (goods vs services) on the relationship between brands’ activities and brand adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 64 publications
(72 reference statements)
1
21
0
1
Order By: Relevance
“…Additionally, Wilk et al 2018 reported that customers -i.e., supporters of a charity who donate -have more impact on consumer (i.e., donor) decision-making than brand-sponsored marketing messages thanks to a process called voluntary brand advocacy. More specifically, people who mention a charity on social media and engage in brand advocacy (on Facebook) are more likely to donate (Wallace et al 2017;Choi et al 2021).…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, Wilk et al 2018 reported that customers -i.e., supporters of a charity who donate -have more impact on consumer (i.e., donor) decision-making than brand-sponsored marketing messages thanks to a process called voluntary brand advocacy. More specifically, people who mention a charity on social media and engage in brand advocacy (on Facebook) are more likely to donate (Wallace et al 2017;Choi et al 2021).…”
Section: Related Workmentioning
confidence: 99%
“…In this respect, it is highly relevant to perform a longitudinal observance of a solvent customer group with a growing impact-Generation Z which is socially aware, e-literate (Turner 2015) and Internet and social media dependent (Bassiouni and Hackley 2014;Choi et al 2021). Generation Z organically continues trends launched by the preceding Generation of Millennials which established the four components cyclic customer journey: connect, explore, buy and use in the context of the real and electronic universe (Mele et al 2021).…”
Section: Theoretical Background-the Carroll's Csr Pyramid Temple Believers and Heretics Before And During The Covid-19 Eramentioning
confidence: 99%
“…At the same time, their determination, social and digital awareness might induce the idea that they will automatically opt for CSR and, if not totally selfish, then they should be ready to pay a CSR bonus (D'Adamo and Lupi 2021; ). However, we should keep in mind that Generation Z is very much oriented towards digital media, spends a great deal of time looking for information posted on various portals or in social media (Choi et al 2021) and considers propositions by various influencers (Gajanova et al 2020). They definitely do not reduce themselves to conventional content analysis of reports (Vourvachis and Woodward 2015).…”
Section: Theoretical Background-the Carroll's Csr Pyramid Temple Believers and Heretics Before And During The Covid-19 Eramentioning
confidence: 99%
See 2 more Smart Citations